Umbilical myiasis with sepsis in a neonate - Mondal, Monojit; Biswas, Tanmoy; Banerji, Nayan; Bose, Sayan; Biswas, Biswajit; Mandal, Pijush Kanti (Asian Journal of Medical Sciences, 2014)
Myiasis is the invasion of host’s tissues by the larval stage (maggot) of non?biting flies. It usually infects domestic and wild animals, but sometimes also affects human and is commonly found in the tropical and subtropical areas. Umbilical myiasis in the neonatal period associated with sepsis is a rare occurrence with few reported cases in the literature. We report a case of a 20?days?old neonate from a rural area of West Bengal, India, presented with neonatal sepsis due to umbilical myiasis caused by larval form of blow fly (Chrysomya megacephala). DOI: http://dx.doi.org/10.3126/ajms.v5i4.10004 Asian Journal of Medical Sciences 2014 Vol.5(4); 106-107